Annual Report on Exchange Arrangements and Exchange Restrictions 2005. (Annual Report on Exchange Arrangements and Exchange Restrictions; 2005, 2005)
The exchange and trade systems of IMF member countries are presented in this comprehensive volume in a tabular format, which includes coverage of the regulatory framework for capital movements. The information generally relates to 2004 but also covers significant developments in early 2005.